2016
DOI: 10.1080/07929978.2016.1200352
|View full text |Cite
|
Sign up to set email alerts
|

Microbial priming elicits improved plant growth promotion and nutrient uptake in pea

Abstract: Legume–microbial interactions focus mainly on Rhizobium. The present study aimed to evaluate the plant growth-promoting (PGP) potential of bacterial and cyanobacterial formulations and variety-specific differences following their inoculation in two varieties of pea (Pisum sativum L.), namely Arkel and GP-17. Providencia sp. PW5–Anabaena laxa CW1 treatment was the most promising, with an 11%–76% increase in defense enzyme activity in both varieties. Interestingly, Arkel responded better in terms of nitrogenase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…also showed promise in terms of the high activity of dehydrogenase and enhancing carbon and polysaccharide content of the soil. Both glomalin and polysaccharides play significant roles in the aggregation and sequestration of organic matter (Purin and Rillig 2007), and our earlier studies in pea crop have shown similar increases in these two parameters (Verma et al 2016).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…also showed promise in terms of the high activity of dehydrogenase and enhancing carbon and polysaccharide content of the soil. Both glomalin and polysaccharides play significant roles in the aggregation and sequestration of organic matter (Purin and Rillig 2007), and our earlier studies in pea crop have shown similar increases in these two parameters (Verma et al 2016).…”
Section: Discussionsupporting
confidence: 53%
“…Analyses of glomalin content due to the application of cyanobacterial strains and biofilms used in this study revealed that they may contain 200-300 lg/g wet weight or 2400-3900 GRSPs/g dry weight (pers. Both glomalin and polysaccharides play significant roles in the aggregation and sequestration of organic matter (Purin and Rillig 2007), and our earlier studies in pea crop have shown similar increases in these two parameters (Verma et al 2016). Being a major component of soil organic matter (as much as 5% of soil C), glomalin is known to be reduced or inhibited when organic C is prevalent, especially under no-till conditions.…”
Section: Discussionmentioning
confidence: 60%
“…The superiority of strain JD-14 ( Acinetobacter pittii ) in this study may be due to increased phosphate solubilization and ACC deaminase activities, as our findings agree with those of Baig et al ( 2012 ), which reported better nutrient uptake for PGPR that displayed phosphate solubilization and ACC deaminase activities than for those that did not. Likewise, Ahmad et al ( 2016a ), Subhashini et al ( 2016 ), and Verma et al ( 2016 ) reported enhanced nutrient content and uptake in different crops with PGPR application.…”
Section: Discussionmentioning
confidence: 94%
“…Certain members of the microbial community play a crucial role in the expression of disease resistance of plants. Mechanisms by which beneficial microorganism protect crop plants from diseases include (a) enhancement of overall vigour (e.g., via nutrient mobilization), (b) direct antagonism via parasitism or antibiosis (feeding directly on phytopathogenic microbes or producing antifungal/antibacterial metabolites), (c) niche exclusion (e.g., competition for resources), and (d) induction of systemic and localized resistance (Conrath et al, ; Shoresh, Harman, & Mastouri, ; Sindhu, Dua, Verma, & Khandelwal, ; Verma, Adak, & Prasanna, ; Xue, ). For instance, Trichoderma belongs to one of the best‐studied genera with antagonistic activity against a wide range of root pathogens (Harman, Howell, Viterbo, Chet, & Lorito, ).…”
Section: Complex Interactions Between Grain Legumes and Their Root‐asmentioning
confidence: 99%
“…To overcome such limitations, it is necessary to consider complex plant-microbe interactions and develop screening systems that account for multiple interactions among pathogens, beneficial microbes, and the host plant genotype. (Conrath et al, 2006;Shoresh, Harman, & Mastouri, 2010;Sindhu, Dua, Verma, & Khandelwal, 2010;Verma, Adak, & Prasanna, 2016;Xue, 2003). For instance, Trichoderma belongs to one of the best-studied genera with antagonistic activity against a wide range of root pathogens (Harman, Howell, Viterbo, Chet, & Lorito, 2004).…”
Section: The Dilemma With Pathogen Complexesmentioning
confidence: 99%